INTEGRATING VIDEO-VIEWING TECHNIQUES TO IMPROVE VOCATIONAL STUDENTS’ ORAL PERFORMANCE - Nurhasanah Halim; Retno Dwigustini; Arrizqi Ramadhan; Susilawati Susilawati; Biyulaika Biyulaika (Jurnal Scientia, 2023)
Although vocational content has been incorporated into the curriculum, more is needed to cater to the needs of nursing students to view the fundamental act of communication when English is essential. The insufficiency might be catered by providing videos/ video clips available in such a global online video sharing and social media platform as Youtube or a library of free videos made by and for teachers and students everywhere as Nextvista.org. Exposing students to authentic language use through video's multimodal characteristics has made it a popular instructional medium. According to Krashen's Input Theory, students can learn best by comprehending messages or getting comprehensible information through authentic material like video clips. Involving fifteen students, this action research took the cyclical model of Kemmis and McTaggart to practice video-viewing techniques to improve their oral performance. Multiple methods of data collection (scoring rubric, collaborator's observation checklist, and semi-structured interview) were employed to portray the extent of oral performance improvement by practicing the techniques. The findings signified that the student's oral performance is enhanced by using the video-viewing technique, and they also feel optimistic about it. They were able to learn in a meaningful way because of the video's real-world setting. It is further advised that English teachers, particularly those who teach technical and vocational schools, employ such contextual techniques and media to give pupils a better learning experience.